Design and development of a hybrid-based mobile app for ISCTE-IUL - Paulino, Fábio (2016)
The increase in mobile computing power and the number of mobile devices available worldwide has led to a considerable increase in applications. Many of these mobile applications are designed to help its users in their daily basis. Some universities saw this increase as an opportunity to help their students in their academic life by creating a mobile application that grants easier access to several services of the institution. In ISCTE-IUL, the decentralization of several services and the lack of compatibility with mobile devices hinder their access to their students which then they require laptops or computers of the institution to access them. The proposal presented in this dissertation is the creation of a mobile application using hybrid technologies in order to provide an easy mean of interaction between students and services of ISCTE-IUL. The results obtained with the students of the institution show that this application is viable and that it is desired by the student community.